Neoplastic cells parasitized by Mycobacterium leprae: report of two cases of melanocytic nevus and one of basal cell carcinoma - Cleverson Soares Teixeira; Patricia Pinheiro Montalvão; Isabella Tostes de Oliveira; Patrick Alexander Wachholz (BMC, 2019)
Abstract Background Leprosy is a major public health concern in many developing countries. Mycobacterium leprae (M. leprae), the causative agent of leprosy, has the ability to parasitize different types of human cells and tissues. In this article, the uncommon parasitism of nevus and neoplastic and epithelial cells by M. leprae are described using histological sections doubly stained by Fite-Faraco (FF) and immunohistochemistry (IHC), respectively. Case presentation Three patients with borderline-lepromatous and lepromatous leprosy underwent excision of melanocytic nevi (cases 1-2) and basal cell carcinoma (case 3). Histological sections confirmed the clinical diagnosis of melanocytic nevus and basal cell carcinoma, but leprosy lesions were evident in adjacent tissues. FF staining and IHC (CD68, Melan A, and 34βE12) demonstrated the presence of bacilli within the nevus cells and also in the epithelial cells of the basal cell carcinoma. Conclusions M. leprae has the ability to parasitize different types of cells, including neoplastic cells. Pathologists working in settings where leprosy is endemic should be aware that some cutaneous biopsy specimens may also present with leprosy findings.